RNASeq analysis of drought-stressed guayule reveals the role of gene transcription for modulating rubber, resin, and carbohydrate synthesis - Chen Dong; Grisel Ponciano; Naxin Huo; Yong Gu; Daniel Ilut; Colleen McMahan (Scientific Reports)
Abstract The drought-adapted shrub guayule (Parthenium argentatum) produces rubber, a natural product of major commercial importance, and two co-products with potential industrial use: terpene resin and the carbohydrate fructan. The rubber content of guayule plants subjected to water stress is higher compared to that of well-irrigated plants, a fact consistently reported in guayule field evaluations. To better understand how drought influences rubber biosynthesis at the molecular level, a comprehensive transcriptome database was built from drought-stressed guayule stem tissues using de novo RNA-seq and genome-guided assembly, followed by annotation and expression analysis. Despite having higher rubber content, most rubber biosynthesis related genes were down-regulated in drought-stressed guayule, compared to well-irrigated plants, suggesting post-transcriptional effects may regulate drought-induced rubber accumulation. On the other hand, terpene resin biosynthesis genes were unevenly affected by water stress, implying unique environmental influences over transcriptional control of different terpene compounds or classes. Finally, drought induced expression of fructan catabolism genes in guayule and significantly suppressed these fructan biosynthesis genes. It appears then, that in guayule cultivation, irrigation levels might be calibrated in such a regime to enable tunable accumulation of rubber, resin and fructan.